B-spline Function Modeling of Electric Heating Flow Regulating Valve. Issue 5 (January 2021) - Zhang, Xingchao; Yang, Chengzhi
Abstract: In this paper we propose a modeling approach of electric heating flow regulating valve with B-spline function and recursive least squares method. And by means of the analysis of the structure and working principle of electric heating flow regulating valve, its correctness is validated with MATLAB simulation. The results indicate that this modeling method can realize the minimum error approximation of real working state of electric heating flow regulating valve.